2022
DOI: 10.1080/22221751.2022.2065937
|View full text |Cite
|
Sign up to set email alerts
|

Exploring surface water as a transmission medium of avian influenza viruses – systematic infection studies in mallards

Abstract: Mallards ( Anas platyrhynchos ) are an abundant anseriform migratory wild bird species worldwide and an important reservoir for the maintenance of low pathogenicity (LP) avian influenza viruses (AIV). They have also been implicated in the spread of high pathogenicity (HP) AIV after spill-over events from HPAIV-infected poultry. The spread of HPAIV within wild water bird populations may lead to viral contamination of natural habitats. The role of small shallow water bodies as a transmissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 58 publications
1
22
0
Order By: Relevance
“…It must be emphasised that the pond and drinking waters were replaced and refreshed daily, hence the levels of H5N1-21 vRNA detection represented accumulation during the preceding 24 hours. It has also been demonstrated that deliberate experimental contamination of water with clade 2.3.4.4 H5N8-2016 isolates from the UK and The Netherlands can result in successful infection of naïve chickens [55], with similar observations having been made for mallards [56].…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…It must be emphasised that the pond and drinking waters were replaced and refreshed daily, hence the levels of H5N1-21 vRNA detection represented accumulation during the preceding 24 hours. It has also been demonstrated that deliberate experimental contamination of water with clade 2.3.4.4 H5N8-2016 isolates from the UK and The Netherlands can result in successful infection of naïve chickens [55], with similar observations having been made for mallards [56].…”
Section: Discussionmentioning
confidence: 70%
“…It must be emphasised that the pond and drinking waters were replaced and refreshed daily, hence the levels of H5N1-21 vRNA detection represented accumulation during the preceding 24 hours. It has also been demonstrated that deliberate experimental contamination of water with clade 2.3.4.4 H5N8-2016 isolates from the UK and The Netherlands can result in successful infection of naïve chickens [55], with similar observations having been made for mallards [56]. By specifically identifying how environmental contamination features in the mechanism of H5Nx clade 2.3.4.4 HPAIV transmission, this study along with others has confirmed the importance of biosecurity to prevent water contamination at poultry premises from becoming a source of infection and onward spread [53, 57].…”
Section: Discussionmentioning
confidence: 96%
“…Yet, the tenacity of AIV in surface water and in sediments is remarkably high for a virion whose infectivity depends on an intact lipid envelope ( 11 15 ). In addition, very few viral particles resuspended in surface water can be sufficient to start an infection, as recently shown by experimental infection studies in mallards ( Anas platyrhynchos ) ( 10 ). This highlights the putative importance of surface water as a transmission medium of AIV.…”
Section: Introductionmentioning
confidence: 87%
“…If infected birds congregate in such water bodies, AIVs could then be excreted in surface water through fecal contamination. This may turn such waters into a highly efficient source of infection ( 10 ). Once present in water, AIV can drift with currents, sink into sediments, or may otherwise be diluted and inactivated by various abiotic and biotic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Waterfowl and other aquatic species have commonly been asymptomatic carriers of LPAIV, presenting with mild enteric infections, which circulate among wild birds. Transmission of LPAIVs primarily occurs via an indirect fecal-oral route involving an environmental exposure, which provides opportunity for spread via shared waterbodies along migratory routes or wintering areas of congregation (Fouchier & Munster 2009;Ramey et al 2020;Ahrens et al 2022). The Gs/GD H5Nx viruses, however, have also evolved to replicate within the respiratory tract and can thus transmit directly through a respiratory route (i.e., respiratory droplets).…”
Section: Avian Influenza Origin and Evolution Of Clade 2344 H5nx Hpaivmentioning
confidence: 99%